The Distortive Effects of Too Big To Fail: Evidence from the Danish Market for Retail Deposits - Iyer, Rajkamal; Lærkholm Jensen, Thais; Johannesen, Niels; Sheridan, Adam (Review of Financial Studies, 2019)
We study the impact of too-big-to-fail (TBTF) guarantees on the market for retail deposits. Exploiting information about all personal deposit accounts in Denmark and salient changes to the deposit insurance limit, we provide evidence that systemically important banks successfully retain and attract uninsured deposits in a crisis at the expense of other banks even as they differentially lower their interest rates. The funding shock suffered by nonsystemic banks causes a decrease in their lending. The results point to the distortive effects of TBTF guarantees in the market for retail deposits. Received March 15, 2018; editorial decision January 15, 2019 by Philip Strahan.